A Fully Automated Synthesis of 14-(R,S)-[18F]fluoro-6-thia-heptadecanoic Acid ([18F]FTHA) on the Elixys Radiosynthesizer - Usevalad Ustsinau; Lukas Nics; Marcus Hacker; Cecile Philippe (MDPI AG, 2024)
14-(R,S)-[18F]fluoro-6-thia-heptadecanoic acid ([18F]FTHA) is a radiocompound for imaging the fatty acid circulation by positron emission tomography. A revived interest in imaging of lipid metabolism led us to a constant tracer production over three years, initially using a conventional vessel-based synthesizer and later transitioning to the cassette-based Elixys synthesizer. On the Elixys module, the radiochemical yield of [18F]FTHA could be increased by more than two times, reaching 13.01 ± 5.63% at the end of the synthesis, while maintaining necessary quality control results.